2021
DOI: 10.1111/1365-2664.13842
|View full text |Cite
|
Sign up to set email alerts
|

Shade‐growing practices lessen the impact of coffee plantations on multiple dimensions of ant diversity

Abstract: Land use management influence changes in biodiversity beyond the targeted species. Management practices in coffee plantations have shifted from coffee growing below accompanying (shade) trees, to intensified monocultures in which coffee grows fully exposed to the sun. Anthropogenic disturbance causes changes in species composition relative to adjacent natural patches and reduces their biotic heterogeneity. Here, we assessed the impact of coffee plantation management practices on the taxonomical, phylogenetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…Shades are an omnipresent source of spatial and temporal microclimatic heterogeneity. Yet, their consequences on species' foraging activity, community structure and their potential role in the local coexistence of native and invasive species are understudied (Stahlschmidt and Johnson 2018;Ibarra-isassi et al 2021). This study is a first step towards understanding how shading conditions could mediate the local coexistence of native and invasive competitors and should stimulate future research to explore the effects of fine-scale environmental heterogeneity on native and invasive species coexistence and how these effects might change 395 across seasons or at other latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Shades are an omnipresent source of spatial and temporal microclimatic heterogeneity. Yet, their consequences on species' foraging activity, community structure and their potential role in the local coexistence of native and invasive species are understudied (Stahlschmidt and Johnson 2018;Ibarra-isassi et al 2021). This study is a first step towards understanding how shading conditions could mediate the local coexistence of native and invasive competitors and should stimulate future research to explore the effects of fine-scale environmental heterogeneity on native and invasive species coexistence and how these effects might change 395 across seasons or at other latitudes.…”
Section: Discussionmentioning
confidence: 99%
“…A larger number of within‐colony replicates could provide a more robust estimation of variance and perhaps affect the variance–environment relationship (Gaudard et al, 2019). Furthermore, colony‐level trait adaptation and plasticity along environmental gradients provides an interesting avenue for future research (Gibb et al, 2022; Ibarra‐Isassi et al, 2021; la Richelière et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reductions in FD and PD in rubber plantation were lower than the null expectation based on random community assembly. These results imply functional and phylogenetic clustering in rubber plantation ant communities, suggesting that strong environmental filtering affects ant community assembly by filtering out ant species/lineages unable to survive in plantations (Liu et al ., 2016; Ibarra‐Isassi et al ., 2021). The eight species detected in rubber plantation represent a unique subset of species detected in rainforest belonging to only four genera: Brachyponera , Monomorium , Nylanderia , and Strumigenys .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with previous findings indicating that limited nesting resources after the conversion of natural forest to monoculture plantations reduces ant abundance and TD (Armbrecht et al ., 2004; Philpott & Foster, 2005; Arenas‐Clavijo & Armbrecht, 2018; Ibarra‐Isassi et al ., 2021). Analysis of ant FD and PD indicated that the loss of species richness in rubber plantation was not random and that the simplified ant communities with limited nesting resources could have negative effects on ecosystem functioning.…”
Section: Discussionmentioning
confidence: 99%